Family presence during resuscitation: A qualitative study of the experiences of families at the emergency medicine directorate of Komfo Anokye Teaching Hospital (KATH), Ghana - Anokyewaa Boadi–Suadwa; Edward Appiah Boateng; Felix Apiribu; Cecilia Amponsem Boateng; Abena Kyerew Abebrese (PLoS ONE, 2026)
Family Presence During Resuscitation (FPDR) is increasingly recognized as a component of patient- and family-centred care, offering emotional support, fostering transparency, and strengthening trust in clinical care. However, in many Sub-Saharan African settings, including Ghana, the practice remains uncommon, undocumented, and lacks policy support. Fewer studies have examined families’ experiences with FPDR than those of clinicians. This study explored the lived experiences of Ghanaian families with witnessed resuscitation of their loved ones in a tertiary hospital in Ghana. A qualitative phenomenological approach was adopted to gain in-depth insights into the emotional, cognitive, and social experiences of family members present during resuscitation. Twelve participants were purposively sampled from the Emergency Medicine Directorate of Komfo Anokye Teaching Hospital (KATH). Data were collected through in-depth interviews and field notes and analyzed using Braun and Clarke’s Reflexive Thematic Analysis. Three major themes emerged: (1) Emotional Rollercoaster – families experienced shock, helplessness, and anxiety; (2) Uncertainty and Information Asymmetry – participants reported confusion and distress due to lack of communication and comprehension of information given; and (3) Decision Making and Consent – families encountered ethical dilemmas and emotional stress when making critical decisions under pressure. These findings reflect the core principles of patient- and family-centred care in the provision of dignity and respect, information sharing, and collaboration. It also highlights the cultural and emotional significance of FPDR in the Ghanaian context.